ответ:
Пошаговое объяснение:
1) 7-3x=6x-56
-3x -6x = -56 -7
-9x= - 63
x=7 ответ: x=7
2)0.9x-7.4= -0.4x+4.3
0,9x+0,4x=4,3+7,4
1,3x=11,7
x=9 ответ: x=9
3)9-7(x+3)=5-6x
9-7x-21=5-6x
-12-7x=5-6x
-7x+6x=5+12
-x= 17
x= -17 ответ: x= -17
4) (7x+9)-(11x-7)=8
7x+9-11x+7=8
-4x+16=8
-4x=8-16
-4x=-8
x=2 ответ: x= 2
6) 3/4 (1/6x - 1/3)= 2x -11/2
Раскрыть скобки, выполнив умножение на 3/4
1/8x-1/4=2x-11/2
x-2=16x-44
x-16x=-44+2
-15x=-42
x= 14/5 ответ: x= 14/5
7) x-2/x-7= 5/8
x-2/x-7= 5/8 ,
8(x-2)=5(x-7)
8x-16=5x-35
8x-5x=-35+16
3x= -19
x= -19/3 ,
x=-19/3 ответ: x=-19/3
Поу словию задачи сказано, что их среднее арифметическое равно 6, значит:
(x+1,5x+2,5x)/3=6
5х/3=6
5х=6*3
5х=18
х=18/5
х=3,6
3,6 - третье число
3,6*1,5=5,4-второе число
3,6*2,5=9-первое число